THE INTERRELATIONSHIP BETWEEN THE MATHEMATIZATION OF SCIENCE AND THE IDEA OF UNIVERSAL FORMAL LANGUAGE OF SCIENCE - Nijole Aukstuolyte (European Scientific Journal, ESJ, 2014)
The paper analyses the development of theoretical thought producingthe idea of the language of mathematics as a universal formal scientificlanguage and consolidating it in the Early Modern epistemological analysisof language. The mathematical reflection of the world as well as the criticalapproach to the natural language with regard to its suitability for thepurposes of cognition highlighted the cognitive significance of signs and theway of their application. That directed the philosophers‘ efforts towards thesearch for the proper language of science. The paper reveals how, reflectingmathematics not only as an instrument of knowledge acquisition and itsorganization model, but also as language, the mastering of which determinesthe possibilities of the study of nature, formalistic investigations of languageraising the problem of the epistemological possibilities of the language ofscience, becomes dominating in the Modern philosophy.